Seventh festival concert, Friday, August 27, 1937, by Vienna Philharmonic - Wiener Philharmoniker:::Creator:::::::::::: (Vienna; Austria, 2020)
Program for a performance by the Vienna Philharmonic at the Salzburg Festival on August 27, 1937, under the direction of Wilhelm Furtwängler, of Beethoven's Ninth Symphony. Includes program notes in German, English, and French.